Behavior and marketing mix that influence service selection of yoga. Of the female working age . Of the female working age in Bangkok Metropolitan Region. - Laptawee, Natthanicha; Khongsawatkiat, Kittiphan (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
This research aims to 1) survey the behaviors in choosing the Yoga service of those female working staff in Bangkok and the suburbs, 2) study the marketing-mix influencing the choosing of the Yoga service of those female working staff in Bangkok and the suburbs, 3) categorize the choosing of the Yoga service of those female working staff in Bangkok and the suburbs based on the personal data and the behaviors, and 4) study the impact of the service marketing-mix influencing the choosing of the Yoga service of those female working staff in Bangkok and the suburbs. The sample in this study, derived through the Cochran sampling technique, are those 400 female working staff. The statistical tools used in data nalysis are Mean, Standard Deviation, Independence t-test, One Way ANOVA, and Stepwise Multiple Regression. It is revealed that most single female working staff responding to the questionnaire are the civil servants aged between 21-30 years old, earning their bachelor degree, having 20,001-30,000 baht as their salary per month. The study on the behaviors in choosing the Yoga service shows that they practice the Yoga for 1-2 years and they usually go with their friends. Their practicing period is between 8.00-12.00 a.m. The data source influencing their decision-making are the leaflets and brochures. They pay for the one-hour-practice around 250-300 baht and the convenient payment channels are the credit cards and the Yoga service-providing places. The reason why they choose to practice the Yoga is because the practicing place is near their offices and those who influence their decision-making are the family members and the Yoga types. The types they like to practice is the JOINT THERAPY type. The first three marketing-mix factors influencing the decision-making of the female working staff are those factors on place, marketing promotion, and the staff respectively. It is found that the choosing of the Yoga service of those female working staff in Bangkok and the suburbs based on the personal data is significantly indifferent while that based on the behavior is mostly found significantly indifferent except those factors on the data source inspiring them to go to the Yoga practicing place, the convenient payment channels, the people influencing their decision-making, the Yoga class, and the Yoga type which are found statistically significant at 0.01 level. The study on the impact of the marketing-mix on the choosing of the Yoga service of those female working staff in Bangkok and the suburbs shows the following causes: the marketing0mix factor (β = 0.41 ) on the physical (β = 0.38), and on the place (β = 0.12) by the equation with the forecasting power at 67%. Article history : Accepted 29 April 2016 SIMILARITY INDEX = 0.00